A U‐shaped association between baseline neutrophil count and COVID‐19‐related mortality: A retrospective cohort study. Issue 7 (12th April 2021) - Fu, Wei; Chen, Chi; Chen, Xin‐Lin; Wang, Kun; Zuo, Peiyuan; Liu, Yuwei; Zhang, Meng; Zhao, Xiaofang; Xie, Songpu; Zhang, Hao; Geng, Yan; Liu, Chengyun
Abstract: Several descriptive studies have reported that higher neutrophil count (NC) may be correlated with poor prognosis in patients with confirmed COVID‐19 infection. However, the findings from these studies are limited by methodology and data analysis. This study is a cohort study. We nonselectively and consecutively collected a total of 663 participants in a Chinese hospital from January 7 to February 28. Standardized and two‐piecewise Cox regression model were employed to evaluate the association between baseline neutrophil count (bNC), neutrophil count change rate (NCR), and death. bNC had a U‐shaped association with death. In the range of 0.1 to ≤1.49 × 10 9 /L (hazard ratio [HR] = 0.19, 95% confidence interval [CI] = 0.05–0.66) and >3.55 × 10 9 /L of bNC (HR = 2.82, 95% CI = 1.19–6.67), the trends on bNC with mortality were opposite. By recursive algorithm, the bNC at which the risk of the death was lower in the range of >1.49 to ≤3.55 × 10 9 /L (HR = 13.64, 95% CI = 0.25–74.71). In addition, we find that NCRs (NCR1 and NCR2) are not associated with COVID‐19‐related deaths. Compared with NCR, bNC has the potential to be used for early risk stratification in patients with COVID‐19 infection. The relationship between bNC and mortality was U‐shaped. The safe range of bNC was 1.64–4.0 × 10 9 /L. Identifying the correlation may be helpful for early risk stratification and medical decision‐making. Highlight: Identifying the safe rage of bNC may be helpful for early risk stratification and medical decision‐making for COVID‐19 patients.